INSTRUMENTOS DE EVALUACIÓN DOCENTE EN LA ASIGNATURA DE MATEMÁTICA, DE LA BÁSICA SUPERIOR EN LA UNIDAD EDUCATIVA PEDRO VICENTE MALDONADO, EL PERÍODO SEPTIEMBRE 2019 – FEBRERO 2020 - Chariguamán Curipallo, Shirley Vanessa (2020)
The research study titled" Teacher evaluation instruments in the mathematics subject, of the upper basic in Unidad Educativa "Pedro Vicente Maldonado", the period September 2019 - February 2020," has shown currently the evaluation instruments constitute an essential element of the curriculum. For this reason, this research determined the importance of the evaluation instruments. To carry out this purpose, each of these tools was investigated in different bibliographic sources. With this information, a survey was carried out; it was applied to the institution's teachers in which was obtained favorable results that helped in a diagnosis that instruments are used to measure the development of the conceptual, procedural, and attitudinal contents in the subject of mathematics. Given the quantitative nature, an exploratory, field, bibliographic, and transversal study was chosen; 13 teachers were the population and the sample. The instruments used to evaluate are the checklist, assessment scale, anecdotal record, graphic organizers, portfolio, projects, questionnaires, debate, written / oral tests, rubric, and class journal. Finally, it is concluded that the instruments most frequently applied to assess academic performance in the subject of mathematics are the rubric, the questionnaire, the presentation, the class journal, and the tests or exams. However, other tools are used less frequently, such as the debate, the essay, the portfolio, the graphic organizers, and the checklist.